1999
DOI: 10.3109/10253899909001119
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Postnatal Manipulation on Central β-Adrenoceptor Transmission

Abstract: Neonatal handling is known to induce long-lasting changes in behavioral and neuroendocrine responses to stress. Since the central noradrenergic system participates in the adaptive responses to stressful conditions we have analyzed the effects of postnatal handling on beta-adrenoceptor binding sites and isoprenaline- and forskolin-stimulated cyclic AMP accumulation in cerebral cortex, hippocampus and cerebellum of rats at 1 and 3 months of age. Handled animals showed reduced emotional reactivity and lower ACTH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
2
9
0
1
Order By: Relevance
“…This effect is comparable to those previously reported in rats, where environmental stimulation produced long-lasting reduction of central noradrenergic responsiveness [67], and postnatal handling induced short- and long-lasting depression of AC functioning [42,43]. This may be explained since EE, when provided early in the life of normal animals, may also serve as a factor capable of moderating stressing responses, thus enabling the animals to cope more properly with learning challenges.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This effect is comparable to those previously reported in rats, where environmental stimulation produced long-lasting reduction of central noradrenergic responsiveness [67], and postnatal handling induced short- and long-lasting depression of AC functioning [42,43]. This may be explained since EE, when provided early in the life of normal animals, may also serve as a factor capable of moderating stressing responses, thus enabling the animals to cope more properly with learning challenges.…”
Section: Discussionsupporting
confidence: 74%
“…Our previous work suggested that the long-lasting adaptation of the AC transduction system was a key element in the effects of neonatal handling in rats [42,43,44], and clear alterations of AC and PLC signaling systems in DS brains. We here aimed to assess the possible changes in G protein signaling systems upon postweaning EE in Ts65Dn mice.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that postnatal handling can differentially modify the binding properties of the badrenoceptor and its primary biochemical response in the young rat brain (Baamonde et al, 1999), emphasizing the role of the central noradrenergic system in the modulation of the behavioural and neuroendocrine responses to postnatal handling. Noradrenaline is involved in the control of emotions and in the reactivity to stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated NA activity enhances anxiety-like behavioral responses and inappropriate activation of the locus coreuleus (LC), may participate in the exaggerated stimulus-responsiveness and increased emotionality seen in patients with stress or anxiety disorders (Priolo et al, 1991;Aston-Jones et al, 1996;Goddard and Charney, 1997). On the other hand, antidepressant treatment, that is effective in panic disorder patients, decreases LC firing and tyrosine hydroxylase (TH, rate-limiting enzyme in the synthesis of catecholamines) expression (Smith et al, 1995), and behavioral manipulations that decrease stress, such as postnatal handling modulate the responses of the noradrenergic system (Escorihuela et al, 1995a,b;Baamonde et al, 1999Baamonde et al, , 2002.…”
mentioning
confidence: 99%